Harnessing Chelonus inanitus for efficient Spodoptera spp. management: Learning about production to explore roles in Baculovirus transmission - Beatriz Dáder; Ariel Morel; Delia Muñoz; Primitivo Caballero; Pilar Medina (Biological Control)
Control of Spodoptera spp. (Lepidoptera: Noctuidae) crop pests has traditionally relied on heavy insecticide use. Baculoviruses (BV) from the genera Alphabaculovirus and Betabaculovirus offer effective, species-specific alternatives for managing their outbreaks. Joint use of BVs with natural enemies, such as parasitoids, could further enhance control of Spodoptera spp. by contributing to virus dispersion. In a series of experiments, we studied the optimal host age and parasitization duration of the endoparasitoid Chelonus inanitus L. (Hymenoptera: Braconidae) for parasitoid production, as well as the parasitoid preference and mechanical transmission of Spodoptera exigua and Spodoptera littoralis multiple nucleopolyhedroviruses (SeMNPV and SpliMNPV). We found that parasitoid progeny production was significantly lower when parasitized eggs were either too young (24 h) or too old (96 h), highlighting the importance of host egg age. Additionally, there was an increasing trend in parasitoid offspring production with longer parasitization exposure times, particularly at 6 and 24 h compared to shorter durations. Chelonus inanitus did not discriminate between SpliMNPV-contaminated and non-contaminated eggs, but had a remarkable preference for SeMNPV-contaminated eggs. The parasitoid effectively dispersed BVs, not only from BV-treated eggs to heathy ones by parasitization, but also, and even more efficiently, by the sole contact with a contaminated surface without eggs. Understanding complex BV-parasitoid interactions is crucial for developing integrated pest management strategies that maximize the efficacy of both parasites.